RETRACTED: Analyzing challenging aspects of IPv6 over IPv4 - Ashraf, Shahzad; Muhammad, Durr; Aslam, Zeeshan (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2020)
The publisher has retracted this article. This article has been retracted at the request of The International Arab Journal of Information Technology (IAJIT) report because of misconduct and plagiarism. The document and its content have been removed from the Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, and reasonable effort should be made to remove all references to this article.